Proportional Preferences in Mesopotamian Architecture - Al Ali, Saba Sami; Handhal, Samar Khadim (Nahrain University College of Engineering Journal, 2016)
Proportion and proportionality have been one of the active concerns in studying the aesthetics of art and architecture. Researchers have always sought for the origin of proportion into the art and Architecture of ancient Egypt and Classical Greece. Studies also have examined Mesopotamian art, but not its architecture. This paper investigates Proportion and proportionality in Mesopotamian architecture. The research is based on the assumption that: any architectural decision concerning the measurements of any major built space was subject to the effect of a symbolically favorite proportion. This proportion is related to the symbolism of numbers, widely known in Mesopotamia. The paper aims to unravel the preferred proportion that was implemented in Mesopotamian architecture, by exploring the proportions of the main inner and outer spaces in several buildings of the neo- Sumerian and old Babylonian epochs during which mathematics flourished and consciousness of numbers got matured.